Ruining Image and the Image as Ruin: William Kentridge’s Trionfi e Lamenti in Rome - Erika Mihálycsa (Babel: Littératures Plurielles)
The essay examines South African visual artist William Kentridge’s monumental erase graffiti frieze Trionfi e Lamenti in Rome (2016), focusing on the artwork’s palimpsestic reworking of a visual archive of Rome and Roman triumphal iconography. Kentridge’s disturbing and ghostly procession along the banks of the river Tiber exploits collage techniques and shows history as a site of continual disasters. The choice of medium for the work – erase graffiti, where the image is literally made of the material of time, the dirt and pollution that accumulate on stone surfaces -– means that the frieze not only (meta)thematizes but also realises finitude and endingness, in so far as the image itself submits to erasement by time, as dirt accumulates. The essay argues that Kentridge’s frieze, an example of radical political art without a clear agenda, allows the image to be submerged in the same partial readability and undecidability that is the condition of ruins and archaeological finds.